OP17 Ethnic differences in ill health and in socioeconomic inequalities in health: population study using 2011 scottish census. (2nd September 2017) - Allik, M; Brown, D; Dundas, R; Leyland, AH
Abstract : Background: Much has been written about high rates of poor health and health inequalities in Scotland, increasingly it is shown how these outcomes vary by ethnicity. Scottish Government has made a policy commitment to understand and address inequalities in health among minority ethnic groups. This study contributes to this by comparing health outcomes and socioeconomic inequalities in health across ethnicities Methods: Two self-reported health measures, poor general health and limiting long-term illness (LLTI), by 5 year age groups, ethnicity and area (Datazones; population mean=815, sd=275) from the 2011 Scottish Census were examined. Ethnicity was self-reported and grouped into 9 main categories. This paper focused on the 5 largest groups: White Scottish (n=4, 445, 678), White British (n=417, 109), White Irish (n=54, 090), Other White (n=167, 530) and Asian (n=140, 678) and ages 0–64. Deprivation was measured using Census based indices and SIMD. Age standardised rates of ill health per 1000 people were calculated for these groups and by deprivation quintiles. Inequalities by area deprivation were measured using the slope index of inequality (SII). Results: For ages 0–64 the standardised rates are lowest for Other Whites and highest for White Scottish for both measures of ill health (LLTI rates respectively 89.1 and 134.9). Differences are greatest for younger adults, LLTI rate for Other Whites aged 15–29 is 32.4, but for White Scottish 71.7, for ages 30–44 these rates are 63.6 and 124.2 respectively. On average White Scottish had poorer health than White British and Irish, both of who are also least likely to live in the most deprived areas. For ages 0–64 inequalities in health were highest for White Scottish (for LLTI the SII=164.4, 95% CI=163.1–165.7), but not much lower for White British (SII=150.8, CI=146.2–155.4) and Irish (SII=145.2, CI=133.6–156.8). Inequalities were much lower among Asians (SII=74.2, CI=64.1–84.1) and among Other Whites (SII=59.3, CI=51.3–66.9). Differences in health inequalities between ethnicities were greatest for ages 30–44. Ill health and inequalities among Asians increased more rapidly for older ages and were similar to White Scottish for those 60+. Results: White Scottish have poorer health compared to other ethnicities, but are also more likely to live in deprived areas compared to White British and Irish. Deprivation affects the health of all ethnicities, but much less so for some groups. Health inequalities are highest among White Scottish, similar for British and Irish, and significantly lower for Asians and Other Whites. This suggests that cultural and/or behavioural factors may reduce the effect of material deprivation on health.